China's growth and the agricultural exports of Southern Africa - Villoria, Nelson; Hertel, Thomas W.; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2009)
The implications of China's growth for the development prospects of Sub-Saharan Africa have been the subject of recent attention. Interest in this topic is motivated by the increasing presence of China in the region and the growing bilateral trade links between China and Africa. Against this background, we herein explore whether China's growth has stimulated agricultural exports in selected countries of Southern Africa, namely, Malawi, Mozambique, Tanzania, the Southern African Custom Union (SACU), and Zambia. We find little complementarity between China's agricultural import demand and the export supply of the focus countries. We also explore whether China affects Southern African agricultural exports through the increases in world agricultural prices associated with China's growing demand for food. We find that although China has moderately increased agricultural prices (in an aggregated sense), Southern African exports do not seem to benefit from these price increases.